Diaphragm and lithium ion secondary battery comprising same
By setting up ceramic strips on the separator of the lithium-ion battery, the migration rate of active ions and the safety performance of the battery are improved, and the problem of insufficient discharge depth of lithium-ion secondary batteries is solved, and the performance and applicable life of the battery are improved.
Patent Information
- Application Number
- CN202411425071.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
When lithium-ion secondary batteries face the demand for large-rate discharge, they often encounter the problem of insufficient available discharge depth, which limits their performance in some application scenarios.
A separator is provided, including a base film and a ceramic strip layer arranged in parallel spaces on at least one side of the base film, to increase the migration rate of active ions in the electrolyte through the gap between the ceramic strip layers and to pass through the width of the ceramic strip layer The matching relationship with the puncture strength of the base film ensures the safety performance of the battery.
This increases the available discharge depth of the battery, keeps it constant under different ambient conditions, reduces the minimum residual power (SOC) level that the battery can effectively power, and expands the applicable environment and life of the battery.
Smart Images

Figure CN119297534A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a diaphragm and a lithium-ion secondary battery comprising the same. Background Art
[0002] As the global energy transition accelerates, especially the demand for clean and efficient energy storage solutions is growing, lithium-ion batteries have become the first choice for new energy storage technology due to their high energy density, long cycle life and fast charging capabilities. Lithium-ion batteries not only play an important role in portable electronic devices such as smartphones and laptops, but also show great potential in large-scale energy storage systems and electric vehicles.
[0003] However, when lithium-ion secondary batteries are faced with the need for high-rate discharge, they often encounter the problem of insufficient available discharge depth, which limits their performance in certain application scenarios. Those skilled in the art strive to improve this technical problem through continuous exploration and improvement, so as to meet the growing demand for high-power and long-time discharge of battery systems. Summary of the invention
[0004] The present application provides a diaphragm, which aims to improve the migration rate of active ions in the electrolyte in the diaphragm to a certain extent, thereby improving the available discharge depth of the battery.
[0005] The present application also provides a battery comprising the above-mentioned separator.
[0006] In a first aspect, the present application provides a diaphragm, the diaphragm comprising a base film and a ceramic strip layer disposed in parallel and spaced apart on at least one side surface of the base film;
[0007] The width of the ceramic strip layer is A, the puncture strength of the base film is N, and the relationship between A and N satisfies: 1 gf / μm≤N / A≤17 gf / μm.
[0008] In a second aspect, the present application provides a battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode; the separator is the separator of the first aspect of the present application.
[0009] In a third aspect, the present application provides a battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode; the separator comprises a base film and a ceramic strip layer arranged in parallel and spaced apart on at least one side surface of the base film;
[0010] The width of the ceramic strip layer is A, the interval width between adjacent ceramic strip layers is B, and the surface resistance of the negative electrode is R;
[0011] A and R satisfy the following relationship: 0.5 μm / mΩ≤A / R≤5 μm / mΩ; and / or, B and R satisfy the following relationship: 0.11 μm / mΩ≤B / R≤2.5 μm / mΩ;
[0012] Among them, 30μm≤A≤100μm, 6.7μm≤B≤50μm, 20mΩ≤R≤60mΩ.
[0013] The technical solution of this application has the following advantages:
[0014] The diaphragm provided by the present application forms a plurality of ceramic strip layers arranged in parallel and at intervals on the surface of the base film. On the one hand, the migration rate of active ions in the electrolyte in the diaphragm is effectively improved through the gaps between the ceramic strip layers; on the other hand, the safety performance of the battery is further guaranteed through the matching relationship between the width of the ceramic strip layers and the puncture strength of the base film, so that the available discharge depth of the secondary battery remains constant under different environmental conditions and will not be affected by extreme conditions. Even when the battery is squeezed or impacted, the available discharge depth of the battery remains unchanged, thereby improving the available discharge depth of the battery and reducing the minimum remaining charge (SOC) level at which the battery can effectively supply power, thereby effectively expanding the applicable environment of the battery and its applicable life.
[0015] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 Schematic diagram of the structure of a diaphragm of the present application, wherein (a) is a top view and (b) is a main view;
[0018] Figure 2 It is a schematic diagram of the structure of another diaphragm of the present application;
[0019] Figure 3 This is a schematic diagram of the structure of another diaphragm of the present application;
[0020] Figure 4 (a)-(b) are respectively partial enlarged images (SEM) of different positions of the diaphragms prepared in Examples 1-2 of the present application;
[0021] The reference numerals are described as follows: 1. base film; 2. ceramic strip layer. DETAILED DESCRIPTION
[0022] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0023] In the description of the present application, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0024] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0025] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0026] The present application provides a diaphragm and a battery, which can increase the migration rate of active ions in an electrolyte, improve the available discharge depth of the battery, and reduce the minimum remaining charge (SOC) level of the battery that can effectively supply power. The technical solution adopted in the present application is as follows.
[0027] In a first aspect, the diaphragm provided in the present application comprises a base film and a ceramic strip layer disposed in parallel and spaced apart on at least one side surface of the base film;
[0028] The width of the ceramic strip layer is A, the puncture strength of the base film is N, and the relationship between A and N satisfies: 1 gf / μm≤N / A≤17 gf / μm.
[0029] It is understandable to those skilled in the art that lithium-ion secondary batteries often encounter the problem of insufficient available discharge depth when facing the demand for high-rate discharge, which limits their performance in certain application scenarios. In order to solve the problem of insufficient available discharge depth of the battery, the diaphragm provided in the present application forms a plurality of ceramic strip layers arranged in parallel and spaced relation on the surface of the base film. On the one hand, the migration rate of active ions in the electrolyte in the diaphragm is effectively improved through the gaps between the ceramic strip layers; on the other hand, the safety performance of the battery is further guaranteed by the matching relationship between the width of the ceramic strip layer and the puncture strength of the base film, so that the available discharge depth of the secondary battery remains constant under different environmental conditions and will not be affected by extreme conditions. Even when the battery is squeezed or impacted, the available discharge depth of the battery remains unchanged, thereby improving the available discharge depth of the battery and reducing the minimum remaining charge (SOC) level that the battery can effectively supply power, thereby effectively expanding the applicable environment of the battery and its service life.
[0030] In an optional embodiment, the relationship between the width A of the ceramic strip layer and the puncture strength N of the base film is as follows: 1gf / μm≤N / A≤17gf / μm, which can achieve the purpose of improving the overcharge pass rate and improving the impact resistance, while maintaining a good available discharge depth. As an exemplary embodiment, the ratio of N / A can be controlled to be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17gf / μm, etc., or within the range of any two of the above values.
[0031] In an optional embodiment, the diaphragm of the present application is provided with the ceramic strip layer, that is, through the gaps between the ceramic strip layers, the migration rate of active ions in the electrolyte in the diaphragm is effectively improved. Therefore, the arrangement direction of each of the ceramic strip layers is not limited, that is, they can be arranged at intervals along the length or width direction of the base membrane, or they can be arranged obliquely at any angle along the base membrane, as long as the width of each ceramic strip layer and the effective spacing between adjacent ceramic strip layers are guaranteed.
[0032] In an optional embodiment, the relationship between the width A of the ceramic strip layer and the puncture strength N of the base film is as follows: 6gf / μm≤N / A≤13gf / μm, which further ensures the overcharge pass rate, impact resistance and good available discharge depth. As an exemplary embodiment, the ratio of N / A can be controlled to be 6, 7, 8, 9, 10, 11, 12, 13gf / μm, etc., or within the range of any two of the above values.
[0033] In an optional embodiment, the width A of the ceramic strip layer satisfies 30-100 μm; the diaphragm provided in the present application can effectively ensure a reasonable spacing gap by adjusting the width A of the ceramic strip layer to 30-100 μm. As an exemplary embodiment, the width A of the ceramic strip layer can be adjusted to 30, 40, 50, 60, 70, 80, 90, 100 μm, etc., or within the range of any two of the above values.
[0034] In an optional embodiment, the puncture strength N of the base film satisfies 100gf-600gf; the diaphragm provided in the present application adjusts the puncture strength N of the base film within the range of 100gf-600gf. The diaphragm described in the present application selects a base film with a high puncture strength, which means that it can better resist the growth of burrs or dendrites inside the battery and improve the pass rate of the battery cell overcharge test; at the same time, the stronger puncture strength can improve the safety of the battery under extreme conditions, such as when the battery is squeezed or impacted. As an exemplary embodiment, the puncture strength N of the base film can be adjusted to 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600gf, etc., or within the range formed by any two of the above values.
[0035] In an optional embodiment, the number of the ceramic strip layers is ≥ 2; it should be noted here that in the diaphragm described in the present application, the number of the ceramic strip layers is not clearly limited, and a reasonable number can be set mainly based on the size of the base membrane, the reasonable width of each ceramic strip layer and the gap between adjacent ceramic strip layers.
[0036] In an optional embodiment, the ceramic strip layers on the surface of the diaphragm are preferably arranged along the length direction or the width direction, and more preferably arranged along the length direction.
[0037] In an optional embodiment, in the diaphragm, the ceramic strip layers are arranged at equal intervals along the surface of the base membrane, which can effectively ensure the uniformity of the gap.
[0038] In an optional embodiment, the thickness of the ceramic strip layer is set to 0.5-5 μm, for example, the thickness of the ceramic strip layer is controlled to be 0.5, 0.8, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 μm, etc., or within the range of any two of the above values.
[0039] In an optional embodiment, the peel strength between the ceramic strip layer and the base film is P, the interval width between adjacent ceramic strip layers is B, and the relationship between P and B satisfies: 0.6×10 6 N / m 2≤P / B≤29.9×10 6 N / m 2 ; preferably, 5×10 6 N / m 2 ≤P / B≤17.9×10 6 N / m 2 ;
[0040] Among them, 6.7μm≤B≤50μm, 30N / m≤P≤200N / m.
[0041] In an optional embodiment, the relationship between the interval width B and the peel strength P satisfies: 0.6×10 6 N / m 2 ≤P / B≤29.9×10 6 N / m 2 ; and preferably set 5×10 6 N / m 2 ≤P / B≤17.9×10 6 N / m 2 This is mainly due to the need to balance the improvement of the spacing coating on the ion conductivity of the battery cell. The appropriate spacing width can achieve better overall performance. As an exemplary embodiment, the P / B ratio can be optimized to be 0.6, 1.0, 3.0, 5.0, 8.0, 10.0, 12.0, 15.0, 17.9, 20.0, 23.0, 25.0, 27.0, 29.9×10 6 N / m 2 In an optional embodiment, the peel strength P can be properly adjusted by changing the amount of adhesive added to the ceramic layer. Generally, when the amount of adhesive is adjusted to be larger, the peel strength is larger.
[0042] In an optional embodiment, the interval width B between adjacent ceramic strip layers is adjusted to 6.7-50 μm; the peel strength P between the ceramic strip layer and the base film is 30-200 N / m. This is mainly because a strong peel strength can ensure that the ceramic layer is not easily separated from the substrate, which means that the coating can remain stable under different environmental conditions, so that the battery can work stably under a wider range of temperature and humidity conditions, so that the available discharge depth of the battery remains constant under different environmental conditions and will not be affected by extreme conditions. For example, when the temperature and humidity conditions change, the available discharge depth of the battery remains unchanged, thereby improving the available discharge depth of the battery and reducing the minimum remaining charge (SOC) level that the battery can effectively supply power. As an exemplary embodiment, the spacing width B between adjacent ceramic strip layers can be selected to be 6.7, 10, 15, 20, 25, 30, 35, 40, 45, 50 μm or within the range formed by any two of the above values; the peel strength P between the ceramic strip layer and the base film can be selected to be 30, 50, 80, 100, 120, 150, 180, 200 N / m or within the range formed by any two of the above values.
[0043] In an optional embodiment, the width of the ceramic strip layer is A, the width of the interval between adjacent ceramic strip layers is B, and the ratio of A to B Q=A / B satisfies: 1.5≤Q≤4.5, wherein 30μm≤A≤100μm, 6.7μm≤B≤50μm. The diaphragm described in the present application optimizes the ratio of the width A of the ceramic strip layer to the width B of the interval between adjacent ceramic strip layers, thereby providing more ion transmission channels while maintaining the heat resistance of the diaphragm and the safety performance of the battery, effectively improving the migration rate of active ions in the electrolyte, and making the available discharge depth of the battery remain constant under different environmental conditions and will not be affected by extreme conditions. For example, when the temperature rises, the available discharge depth of the battery remains unchanged, thereby improving the charge and discharge efficiency of the battery, reducing the minimum remaining capacity (SOC) level that the battery can effectively supply power, and effectively improving the available discharge depth of the battery. As an exemplary implementation, the ratio of A / B may be optimized to be 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 or within a range formed by any two of the above values.
[0044] In an optional embodiment, the width and spacing of the ceramic strip layer are optimized according to different cell structures and different base film materials. The ceramic strip layer coating provides more ion transmission channels for the battery charge and discharge process, effectively improves the migration rate of active ions in the electrolyte, thereby improving the battery charge and discharge efficiency, effectively improving the available discharge depth of the battery, reducing the minimum remaining power (SOC) level that the battery can effectively supply power, and increasing the performance and reliability of the battery under high-rate working conditions.
[0045] In an optional embodiment, the ceramic strip layer includes ceramic particles, the particle size Dv50 of the ceramic particles is D, and the relationship between Q(A / B) and D satisfies: 0.05μm≤D / Q≤1.4μm; preferably, 0.09μm≤D / Q≤0.67μm, which can effectively improve the discharge depth of the battery, reduce the minimum remaining power (SOC) level that the battery can effectively supply power, and contribute to the long-term stable operation of the battery. As an exemplary embodiment, the D / Q ratio can be optimized to be 0.05, 0.09, 0.2, 0.3, 0.4, 0.5, 0.6, 0.67, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4μm or within the range of any two of the above values.
[0046] In an optional embodiment, the particle size Dv50 of the ceramic particles is D, preferably adjusted to 0.1 μm ≤ D ≤ 2.5 μm, more preferably 0.3 μm ≤ D ≤ 1.7 μm. As an exemplary embodiment, the particle size Dv50 of the ceramic particles is adjusted to 0.1, 0.3, 0.5, 1.0, 1.5, 1.7, 2.0, 2.5 μm or within the range of any two of the above values. The main consideration here is that too large a ceramic particle size will affect the coating density and uniformity, and affect the ion transmission efficiency; while too small a particle size of the ceramic particles will affect the hardness of the ceramic coating and the mechanical strength of the diaphragm.
[0047] In an optional embodiment, the ceramic particles are preferably considered to be a mixture of ceramic particles of different particle sizes. This is mainly because the use of small-particle ceramic coating can form a more uniform and dense coating, which reduces the ion transmission efficiency and significantly improves the internal resistance of the battery cell. Therefore, the amount of ceramic coverage can be appropriately reduced in the application; while large ceramic particles can increase the hardness of the coating and improve the mechanical strength of the diaphragm. At the same time, the gap between particles is larger, which can provide more ion transmission channels and improve the battery charging and discharging efficiency. However, due to the poor density of the coating and the loose distribution between particles, it is necessary to increase the coating amount to maintain the structural stability of the coating.
[0048] In an optional embodiment, the ceramic strip layer includes ceramic particles and a binder; preferably, based on the total amount of the ceramic strip layer, the ceramic strip layer includes: 40wt%-97wt% of ceramic particles and 3wt%-60wt% of the binder.
[0049] In an optional embodiment, the ceramic slurry coated to form the ceramic strip layer includes, in total, 40wt%-96wt% of ceramic particles, 3wt%-60wt% of binder, and 0.7wt%-3wt% of dispersant.
[0050] In an optional embodiment, the ceramic particles include one or more of boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon dioxide (SiO2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), cerium oxide (CeO2), zirconium titanate (SrTiO3), barium titanate (BaTiO3), and magnesium fluoride (MgF2);
[0051] In an optional embodiment, the binder includes one or more of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of vinylidene fluoride-trichloroethylene, polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, styrene-butadiene rubber, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polytetrafluoroethylene or polyhexafluoropropylene;
[0052] In an optional embodiment, the dispersant includes one or both of carboxymethyl cellulose and polyvinyl alcohol.
[0053] In an optional embodiment, the elongation at break TD of the base film is 20%-200%, such as 30, 50, 80, 100, 120, 150, 180, 200%.
[0054] In an optional embodiment, the elongation at break MD of the base film is 50%-300%, such as 50, 80, 100, 120, 150, 180, 200, 250, 300%.
[0055] In an optional embodiment, the puncture strength of the base film is 100 gf-600 gf, such as 100, 200, 300, 400, 500, 600 gf.
[0056] In an optional embodiment, the peel strength between the base film and the ceramic strip layer is 30-200 N / m, such as 30, 50, 80, 100, 120, 150, 180, 200 N / m.
[0057] In an optional embodiment, the base film has a thickness of 4-20 μm, for example, 4, 8, 10, 12, 15, 18, 20 μm or within a range formed by any two of the above values.
[0058] In an optional embodiment, the base film includes at least one of a woven film, a nonwoven film, a polyolefin film or a separator paper. As an exemplary embodiment, the polyolefin film includes at least one of polyethylene, polypropylene or a composite material of polyethylene-polypropylene.
[0059] In a second aspect, the present application provides a lithium-ion secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the separator is the separator described in the first aspect of the present application.
[0060] In an optional embodiment, the surface resistance of the negative electrode is R; A and R satisfy the following relationship: 0.5μm / mΩ≤A / R≤5μm / mΩ. The present application has found that when 0.5μm / mΩ≤A / R≤5μm / mΩ is satisfied, the discharge depth of the battery can be effectively increased and the minimum remaining charge (SOC) level that the battery can effectively supply power can be reduced. As an exemplary embodiment, A / R can be adjusted to 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0μm / mΩ or within the range of any two of the above values.
[0061] In an optional embodiment, the surface resistance of the negative electrode is R; B and R satisfy the following relationship: 0.11 μm / mΩ≤B / R≤2.5 μm / mΩ, and the battery also has a better available discharge depth. As an exemplary embodiment, A / R can be adjusted to 0.11, 0.3, 0.5, 1.0, 1.2, 1.5, 1.8, 2.0, 2.5 μm / mΩ or within the range of any two of the above values.
[0062] In an optional embodiment, the surface resistance R of the negative electrode is 20-60mΩ; generally, the negative electrode sheet surface resistance is a strongly correlated factor that determines the available discharge depth of the battery, which is mainly affected by the active material composition and particle size, conductive agent and binder used. The larger the surface resistance, the more unfavorable the battery discharge is, and the available discharge depth of the battery will be deteriorated. As an exemplary embodiment, the surface resistance of the negative electrode is 20, 25, 30, 35, 40, 45, 50, 55, 60mΩ or within the range of any two of the above values.
[0063] In an optional embodiment, in the battery, the positive electrode includes a positive electrode tab groove, and the negative electrode includes a negative electrode tab groove; the aspect ratio of the positive electrode tab groove is q1, and the aspect ratio of the negative electrode tab groove is q2, and the min<q1,q2> The value of is q, and the q and Q values satisfy the following relationship: Q / q = 0.4-6.7 mm -1 This application study shows that when Q / q meets 0.4-6.7mm -1range, the available discharge depth of the battery can be effectively improved and the minimum remaining charge (SOC) level at which the battery can effectively supply power can be reduced.
[0064] In an optional embodiment, the aspect ratio q1 of the tab slot of the positive pole tab is 0.67-3.75, and the aspect ratio q2 of the tab slot of the negative pole tab is 0.67-6. As an exemplary embodiment, the aspect ratio q1 of the tab slot of the positive pole tab is controlled to be 0.67, 1.00, 1.50, 1.80, 2.00, 2.50, 2.80, 3.00, 3.50, 3.75 or in the range of any two of the above values. As an exemplary embodiment, the aspect ratio q2 of the tab slot of the negative pole tab is controlled to be 0.67, 1.00, 1.50, 1.80, 2.00, 2.50, 2.80, 3.00, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00 or in the range of any two of the above values.
[0065] In an optional embodiment, in the battery, the width of the lug groove of the positive pole lug and / or the negative pole lug is 5-15 mm independently of each other; the length of the lug groove of the positive pole lug and / or the negative pole lug is 10-30 mm independently of each other. This is mainly considered that the lug groove size is a strongly related factor affecting the charging and discharging capacity of the battery. If the lug groove size is designed to be too small, it is often not conducive to the effective charging and discharging of the battery and deteriorates the charging and discharging efficiency of the battery; and if the lug groove size is designed to be too large, the capacity of the battery cell will be lost. As an exemplary embodiment, the width of the lug groove of the positive pole lug can be selected as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 mm or within the range of any two of the above values; the length of the lug groove of the positive pole lug can be selected as 10, 15, 18, 20, 25, 30 mm or within the range of any two of the above values. As an exemplary embodiment, the width of the tab slot of the negative electrode tab may be selected to be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 mm or within the range formed by any two of the above values; the length of the tab slot of the negative electrode tab may be selected to be 10, 15, 18, 20, 25, 30 mm or within the range formed by any two of the above values.
[0066] In a third aspect, the present application provides a battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the separator comprises a base film and a ceramic strip layer disposed in parallel and spaced apart on at least one side surface of the base film;
[0067] In an optional embodiment, the surface resistance of the negative electrode is R; A and R satisfy the following relationship: 0.5μm / mΩ≤A / R≤5μm / mΩ. The present application has found that when 0.5μm / mΩ≤A / R≤5μm / mΩ is satisfied, the discharge depth of the battery can be effectively increased and the minimum remaining charge (SOC) level that the battery can effectively supply power can be reduced. As an exemplary embodiment, A / R can be adjusted to 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0μm / mΩ or within the range of any two of the above values.
[0068] In an optional embodiment, the surface resistance of the negative electrode is R; B and R satisfy the following relationship: 0.11 μm / mΩ≤B / R≤2.5 μm / mΩ, and the battery also has a better available discharge depth. As an exemplary embodiment, A / R can be adjusted to 0.11, 0.3, 0.5, 1.0, 1.2, 1.5, 1.8, 2.0, 2.5 μm / mΩ or within the range of any two of the above values.
[0069] In an optional embodiment, the width A of the ceramic strip layer satisfies 30-100 μm; the diaphragm provided in the present application can effectively ensure a reasonable spacing gap by adjusting the width A of the ceramic strip layer to 30-100 μm. As an exemplary embodiment, the width A of the ceramic strip layer can be adjusted to 30, 40, 50, 60, 70, 80, 90, 100 μm, etc., or within the range of any two of the above values.
[0070] In an optional embodiment, the interval width B between adjacent ceramic strip layers is adjusted to 6.7-50 μm. As an exemplary embodiment, the interval width B between adjacent ceramic strip layers can be selected to be 6.7, 10, 15, 20, 25, 30, 35, 40, 45, 50 μm or within a range of any two of the above values.
[0071] In an optional embodiment, the surface resistance R of the negative electrode is 20-60mΩ; generally, the negative electrode sheet surface resistance is a strongly correlated factor that determines the available discharge depth of the battery, which is mainly affected by the active material composition and particle size, conductive agent and binder used. The larger the surface resistance, the more unfavorable the battery discharge is, and the available discharge depth of the battery will be deteriorated. As an exemplary embodiment, the surface resistance of the negative electrode is 20, 25, 30, 35, 40, 45, 50, 55, 60mΩ or within the range of any two of the above values.
[0072] In an optional embodiment, in the battery, the positive electrode includes a positive electrode tab groove, and the negative electrode includes a negative electrode tab groove; the aspect ratio of the positive electrode tab groove is q1, and the aspect ratio of the negative electrode tab groove is q2, and the min<q1,q2> The value of is q, and the q and Q values satisfy the following relationship: Q / q = 0.4-6.7 mm -1 This application study shows that when Q / q meets 0.4-6.7mm -1 range, the available discharge depth of the battery can be effectively improved and the minimum remaining charge (SOC) level at which the battery can effectively supply power can be reduced.
[0073] In an optional embodiment, the aspect ratio q1 of the tab slot of the positive pole tab is 0.67-3.75, and the aspect ratio q2 of the tab slot of the negative pole tab is 0.67-6. As an exemplary embodiment, the aspect ratio q1 of the tab slot of the positive pole tab is controlled to be 0.67, 1.00, 1.50, 1.80, 2.00, 2.50, 2.80, 3.00, 3.50, 3.75 or in the range of any two of the above values. As an exemplary embodiment, the aspect ratio q2 of the tab slot of the negative pole tab is controlled to be 0.67, 1.00, 1.50, 1.80, 2.00, 2.50, 2.80, 3.00, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00 or in the range of any two of the above values.
[0074] In an optional embodiment, in the lithium-ion secondary battery, the width of the tab groove of the positive tab and / or the negative tab is 5-15 mm independently of each other; the length of the tab groove of the positive tab and / or the negative tab is 10-30 mm independently of each other. This is mainly considered that the tab groove size is a strongly related factor affecting the battery's charge and discharge capacity. If the tab groove size is designed too small, it is often not conducive to the effective charge and discharge of the battery and deteriorates the battery's charge and discharge efficiency; and if the tab groove size is designed too large, the capacity of the battery cell will be lost. As an exemplary embodiment, the width of the tab groove of the positive tab can be selected as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 mm or in the range of any two of the above values; the length of the tab groove of the positive tab can be selected as 10, 15, 18, 20, 25, 30 mm or in the range of any two of the above values. As an exemplary embodiment, the width of the tab slot of the negative electrode tab may be selected to be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 mm or within the range formed by any two of the above values; the length of the tab slot of the negative electrode tab may be selected to be 10, 15, 18, 20, 25, 30 mm or within the range formed by any two of the above values.
[0075] It will be understood by those skilled in the art that the battery described in the present application includes a positive electrode, a negative electrode, a separator and an electrolyte. As an example, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer, the positive electrode collector has two surfaces opposite to each other in the thickness direction thereof, and the positive electrode active material layer is disposed on any one or both of the two surfaces opposite to the positive electrode collector. The materials, composition and manufacturing methods of the positive electrode plates used in the lithium-ion secondary battery of the present application may include any technology disclosed in the prior art. As an example, the negative electrode plate includes a negative electrode collector and a negative electrode active material layer, the negative electrode collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode active material layer is disposed on any one or both of the two surfaces opposite to the negative electrode collector. The materials, composition and manufacturing methods of the negative electrode plates used in the lithium-ion secondary battery of the present application may include any technology disclosed in the prior art.
[0076] The electrolyte used in the battery of the present application may include any technology disclosed in the prior art.
[0077] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage content.
[0078] In the following embodiments of the present application, corresponding technical solutions and technical effects are described based on lithium-ion secondary batteries as an example, but the solutions described in the present application can still be applied to other feasible battery systems.
[0079] like Figure 1 As shown in the structure, the lithium-ion battery isolation membrane described in the present application includes a base membrane 1 and a plurality of ceramic strip layers 2 arranged on at least one surface of the base membrane 1, wherein the ceramic strip layers 2 are coated and arranged in parallel along the length direction of the base membrane, and each of the ceramic strip layers 2 is evenly and equally spaced on the surface of the base membrane 1.
[0080] In this embodiment, Figure 1 In the diaphragm shown, the coating method for forming the ceramic strip layer includes:
[0081] (1) preparing ceramic slurry: mixing ceramic material, binder, dispersant and solvent to obtain ceramic slurry;
[0082] (2) The ceramic slurry obtained in step (1) is coated on one side or both sides of the base film layer by roller coating, and after high-temperature baking, a base film layer coated with a ceramic layer on one side or a base film layer coated with a ceramic layer on both sides is obtained.
[0083] A ceramic slurry system such as a conventional system in the art, wherein the ceramic slurry system is prepared as follows: the ceramic material is boehmite, Dv50 is 0.3 μm, the binder is selected from polymethyl methacrylate, the dispersant is ethylene oxide, and the solvent is water; the mass ratio of the ceramic material, the binder, the dispersant and the solvent is 35%:4%:1%:60%.
[0084] The present application also provides another diaphragm with a structure such as Figure 2 As shown in the structure, the lithium-ion battery isolation membrane described in the present application includes a base membrane 1 and a plurality of ceramic strip layers 2 arranged on at least one surface of the base membrane 1, wherein the ceramic strip layers 2 are coated and arranged in parallel along the width direction of the base membrane, and each of the ceramic strip layers 2 is evenly and equally spaced on the surface of the base membrane 1.
[0085] In this embodiment, Figure 2 In the diaphragm shown in FIG. 1 , the coating method for forming the ceramic strip layer is the same as that of Figure 1 The preparation method of the diaphragm shown.
[0086] The present application also provides another diaphragm with a structure such as Figure 3 As shown in the structure, the lithium-ion battery isolation membrane described in the present application includes a base membrane 1 and a plurality of ceramic strip layers 2 arranged on at least one surface of the base membrane 1, wherein the ceramic strip layers 2 are coated and arranged parallel to the inclination direction of the base membrane, and the inclination angle is not limited, and each of the ceramic strip layers 2 is evenly and equally spaced on the surface of the base membrane 1.
[0087] In this embodiment, Figure 3 In the diaphragm shown in FIG. 1 , the coating method for forming the ceramic strip layer is the same as that of Figure 1 and 2 The preparation method of the diaphragm shown.
[0088] In the following embodiments of the present application, the lithium ion secondary battery adopts the present application as shown in the attached Figure 1 or attached Figure 2 or attached Figure 3 The separator shown, other components of the lithium-ion secondary battery, such as the positive electrode, the negative electrode and the electrolyte, can be selected according to the conventional system in the art.
[0089] As an exemplary scheme, the method for preparing a lithium-ion secondary battery described in the following embodiments includes the following steps.
[0090] (1) Preparation of positive electrode sheets for lithium-ion secondary batteries
[0091] First, lithium cobalt oxide is used as an active material and mixed with Super-P conductive agent and activated carbon in a mass ratio of 1:1. Then, PVDF is added as a binder and dissolved in N-methylpyrrolidone solvent at a ratio of 97.5% active material, 1.35% conductive agent and 1.15% binder to ensure uniform mixing. After that, the obtained positive electrode slurry is evenly coated on both sides of the aluminum foil current collector and dried to form a positive electrode film. Finally, the production of lithium-ion battery positive electrode sheets is completed through the steps of cold pressing, cutting into sheets and welding electrode ears.
[0092] (2) Preparation of negative electrode sheets for lithium-ion secondary batteries
[0093] First, graphite is used as an active material and mixed with Super-P conductive agent, CMC thickener and SBR binder, with a mass ratio of 97.1% graphite, 0.6% conductive agent, 1.0% thickener and 1.2% binder. These materials are dissolved in deionized water and stirred thoroughly to form a negative electrode slurry. Then, the negative electrode slurry is evenly coated on both sides of the copper foil current collector and dried to form a negative electrode film. Finally, the preparation of the negative electrode sheet of the lithium-ion battery is completed by cold pressing, cutting into sheets and welding the electrode ears.
[0094] (3) Preparation of electrolyte for lithium-ion secondary batteries
[0095] LiPF6 was selected as the lithium salt, and ethylene carbonate, diethyl carbonate, methyl ethyl carbonate and vinylene carbonate were mixed in a mass ratio of 8:85:5:2 to form a mixed solvent. Subsequently, the lithium salt and the solvent were mixed in a mass ratio of 8:92 to form an electrolyte, which was specifically used for lithium-ion batteries.
[0096] (4) Provide a rechargeable lithium battery comprising the above material
[0097] The separator is the separator prepared in step (1), and the prepared positive electrode sheet, negative electrode sheet and manufactured separator are wound and assembled into a battery cell. After drying, liquid injection and packaging, a lithium-ion secondary battery is obtained.
[0098] Example 1
[0099] The diaphragm described in this embodiment is as shown in the attached Figure 1 As shown, the base film is a polyethylene microporous film, the thickness D of the base film layer is 7 μm, and the puncture strength is 300 gf.
[0100] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the Dv50 of the ceramic particles is selected to be 0.3 μm, the coating thickness of the ceramic strip layer is controlled to be 1.5 μm, the peel strength of the ceramic strip layer is 120 N / m, and the width A and the interval width B of the ceramic strip layer are respectively shown in Table 1 below.
[0101] The local enlarged images (SEM) of different positions of the prepared diaphragms in Examples 1-2 are shown in the attached drawings. Figure 4 As shown in (a)-(b) in the figure, it can be seen that this is a partial enlarged view of the striped ceramic coated diaphragm. The microstructure of the ceramic stripes is highlighted. From the SEM, it can be seen that the ceramic layer is periodically distributed on the surface of the substrate, with a stripe width of 50μm and an interval width of 20μm. Such a structure can effectively increase the migration rate of active ions in the electrolyte, improve the effective discharge depth of the battery, and reduce the minimum remaining charge (SOC) level at which the battery can effectively supply power.
[0102] The separator described in this embodiment is assembled according to the exemplary method of the lithium-ion secondary battery described above, and the minimum remaining capacity (SOC) of the lithium-ion secondary battery that can effectively supply power in each embodiment is tested, that is, the battery cell is wrapped with foam, the surface temperature of the battery cell is monitored, and the SOC value of the battery cell discharged for 15 seconds under different temperature and normal humidity environments is tested. The specific test method is as follows:
[0103] (1) Adjust the furnace temperature to 25°C and leave for 5 minutes;
[0104] (2) 0.5C discharge lower limit voltage;
[0105] (3) Leave for 15 minutes;
[0106] (4) 1.8C constant current charging to the upper limit voltage, cut-off current 0.05C; leave for 30 minutes;
[0107] (5) Repeat the above steps (2) to (4) to produce C0;
[0108] (6) Adjust the furnace temperature to 0°C and leave for 120 minutes;
[0109] (7) 7.5C constant current discharge for 15s, sampling frequency (100ms);
[0110] (8) Leave for 30 minutes;
[0111] (9) 1C discharge adjustment to target SOC;
[0112] (10) Leave for 90 min;
[0113] (11) Repeat the above process (7)-(10), and change the SOC in (7) to the required SOC at the temperature until the discharge cut-off voltage is lower than the lower limit voltage at the target temperature and SOC.
[0114] In this embodiment, the test results of various implementation methods are shown in Table 1 below.
[0115] Table 1 Effect of the width (A) and spacing width (B) of the ceramic strip layer
[0116]
[0117] From the above-mentioned embodiments 1-1 to 1-11, and comparative examples 1-1 to 1-3, it can be seen that the diaphragm described in the present application controls the width A of the ceramic strip layer to be 30-100 μm, and the spacing width B to be 6.7-50 μm. By reasonably setting the gap width between the ceramic strip layers, the migration rate of active ions in the electrolyte in the diaphragm can be effectively improved. In particular, by optimizing and adjusting the ratio of the width A and the spacing width B to 1.5≤A / B≤4.5, while maintaining the heat resistance of the diaphragm and the safety performance of the battery, more ion transmission channels can be provided, and the migration rate of active ions in the electrolyte can be effectively improved, so that the available discharge depth of the battery remains constant under different environmental conditions and will not be affected by extreme conditions. For example, when the temperature rises, the available discharge depth of the battery remains unchanged, thereby improving the charge and discharge efficiency of the battery, reducing the minimum remaining power (SOC) level that the battery can effectively supply power, and effectively improving the available discharge depth of the battery.
[0118] It can be seen from the above-mentioned Examples 1-1 to 1-5, Comparative Examples 1-1 and 1-3 that the width A of the ceramic strip layer will affect the minimum remaining capacity (SOC) level that the battery can effectively supply power. When the width A of the ceramic strip layer is selected to be within the scope of the present application, the battery can achieve a smaller effective power supply remaining capacity (SOC) and have a better available discharge depth.
[0119] From the above-mentioned Example 1-1, Example 1-9 to Example 1-11, and Comparative Example 1-4, it can be seen that the interval width B of the ceramic strip layer will affect the minimum remaining capacity (SOC) level of the battery that can effectively supply power. When the interval width B is selected to be greater than 6.7 μm, the battery can achieve a smaller effective power supply remaining capacity (SOC) and has a better available discharge depth. Similarly, from Example 1-5 to Example 1-8, and Comparative Example 1-2, it can be seen that when the interval width (B) is selected to be less than 50 μm, the battery can achieve a smaller effective power supply remaining capacity (SOC).
[0120] Furthermore, the data in the above table show that optimizing and controlling the A / B ratio will affect the minimum remaining power (SOC) level of the battery that can effectively supply power. From Examples 1-1 to 1-11 and Comparative Examples 1-1 to 1-4, it can be seen that when the A / B ratio is within the scope of the present application, the battery can achieve a smaller effective remaining power (SOC) and have a better available discharge depth.
[0121] Example 2
[0122] The diaphragm described in this embodiment is as shown in the attached Figure 1 As shown, the base film is a polyethylene microporous film (same as Example 1), the thickness D of the base film layer is 7 μm, and the puncture strength is 300 gf.
[0123] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the coating thickness of the ceramic strip layer is controlled to be 1.5 μm, the peel strength of the ceramic strip layer is 120 N / m, and the width A of the ceramic strip layer, the interval width B and the particle size Dv50 of the ceramic particles are respectively shown in Table 2 below.
[0124] The separator described in this example is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the minimum remaining capacity (SOC) (0° C.) that the lithium-ion secondary battery can effectively supply power for each embodiment is tested respectively, and the specific method is the same as that of Example 1.
[0125] In this embodiment, the test results of various implementation methods are shown in Table 2 below.
[0126] Table 2 Relationship between width ratio A / B and ceramic particle size Dv50 Influence results
[0127]
[0128]
[0129] It can be seen from the data in the above table that when the diaphragm described in the present application controls the ceramic strip layer width A, the interval width B and the ceramic particle size Dv50 to satisfy 0.05μm≤Dv50 / (A / B)≤1.4μm, and more appropriately adjusts 0.09μm≤D / Q≤0.67μm, the discharge depth of the battery can be effectively improved, and the battery can achieve a smaller effective power supply remaining capacity (SOC), which is conducive to the long-term stable operation of the battery.
[0130] It can be seen from the data in the above table that the ratio of the width A and the interval width B of the ceramic strip layer described in the present application is 1.5≤A / B≤4.5. When the ceramic particle size Dv50 is 0.1μm-2.5μm, the use of small-particle ceramic coating can form a more uniform and dense coating, which reduces the ion transmission efficiency and significantly improves the internal resistance of the battery cell. Therefore, the ceramic coverage amount can be appropriately reduced in the application; large ceramic particles can increase the hardness of the coating and improve the mechanical strength of the diaphragm. At the same time, the larger the gap between the particles, the more ion transmission channels can be provided, and the battery charging and discharging efficiency can be improved. However, due to the deterioration of the density of the coating and the loose distribution between the particles, the coating amount needs to be increased to maintain the structural stability of the coating.
[0131] Example 3
[0132] The diaphragm described in this embodiment is as shown in the attached Figure 1As shown, the base film is a polyethylene microporous film (same as Example 1), and the thickness D of the base film layer is 7 μm.
[0133] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the Dv50 of the ceramic particles is selected to be 0.3μm, the coating thickness of the ceramic strip layer is controlled to be 1.5μm, the spacing width B of the ceramic strip layer is adjusted according to A, and A / B is controlled to be 4.5. The peeling strength of the ceramic strip layer is 120N / m. The width A of the ceramic strip layer and the puncture strength N of the base film are respectively shown in Table 3 below.
[0134] The separator described in this embodiment is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the minimum remaining capacity (SOC) of the lithium-ion secondary battery that can effectively supply power in each embodiment is tested respectively, and the specific method is the same as that in Example 1.
[0135] The separator described in this embodiment is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the overcharge test effect of the lithium-ion secondary battery in each embodiment is tested respectively. The specific method is as follows:
[0136] (1) The battery cell is discharged at 0.5C to the lower limit voltage at room temperature, fully charged at 1C, and cut off at 0.05C, and the internal resistance data of the full charge voltage is measured;
[0137] (2) The battery cell is charged using CCCV method, 6C-5.04V. The experiment is stopped when the battery is continuously charged for more than 24h. The temperature is monitored during the process and the battery cell pass rate is fed back after the test.
[0138] In this embodiment, the test results of various implementation methods are shown in Table 3 below.
[0139] Table 3 The relationship between the width of the ceramic strip layer A and the base film puncture strength N affects the results
[0140]
[0141] It can be seen from the data in the above table that the diaphragm described in the present application adjusts the relationship between the width A of the ceramic strip layer and the puncture strength N of the base film to be 1gf / μm≤N / A≤17gf / μm, and more preferably 6gf / μm≤N / A≤13gf / μm, which effectively ensures the safety performance of the battery, so that the available discharge depth of the secondary battery remains constant under different environmental conditions and will not be affected by extreme conditions. Even when the battery is squeezed or impacted, the available discharge depth of the battery remains unchanged, thereby improving the available discharge depth of the battery and reducing the minimum remaining power (SOC) level that the battery can effectively power, thereby effectively expanding the applicable environment of the battery and its applicable life.
[0142] It can be seen that in the diaphragm described in the present application, the relationship between the width A of the ceramic strip layer and the puncture strength N of the base film is adjusted to be 1gf / μm≤N / A≤17gf / μm, more preferably 6gf / μm≤N / A≤13gf / μm, and the width A of the ceramic strip layer is further controlled to be 30-100μm, and the puncture strength N of the substrate is in the range of 100gf-600gf. The high puncture strength of the base film means that it can better resist the growth of burrs or dendrites inside the battery and improve the pass rate of the overcharge test of the battery cell; at the same time, the stronger puncture strength can improve the safety of the battery under extreme conditions, such as when the battery is squeezed or impacted, and can further achieve the purpose of improving the overcharge pass rate without losing the discharge depth at the same time.
[0143] Example 4
[0144] The diaphragm described in this embodiment is as shown in the attached Figure 1 As shown, the base film is a polyethylene microporous film (same as Example 1), the thickness D of the base film layer is 7 μm, and the puncture strength is 300 gf.
[0145] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the Dv50 of the ceramic particles is selected to be 0.3μm, the coating thickness of the ceramic strip layer is controlled to be 1.5μm, the spacing width B of the ceramic strip layer is adjusted according to A, and A / B is controlled within the range of 2-4.5. The spacing width B of the ceramic strip layer and the ceramic strip layer peeling strength P of the base film are respectively shown in Table 4 below.
[0146] The diaphragm described in this embodiment is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the minimum remaining capacity (SOC) that the lithium-ion secondary battery can effectively power in each implementation scheme is tested, including the SOC values at 0°C, normal humidity environment and 45°C, 95% RH. The specific method refers to Example 3.
[0147] In this embodiment, the furnace temperature pass rate of each diaphragm is tested respectively. The specific furnace temperature test method is as follows: the battery cell is discharged at 0.5C and fully charged at 1C standard; the voltage / internal resistance / thickness is tested; the battery cell is placed in a hot box and the temperature is raised to 130°C at a rate of (5°C±2°C) / min and maintained for 60 minutes. After the experiment is completed, the battery cell status before and after the test is recorded.
[0148] In this embodiment, the test results of various implementation methods are shown in Table 4 below.
[0149] Table 4 The relationship between the spacing width B of the ceramic strip layer and the peel strength P affects the results
[0150]
[0151] It can be seen from the results in the above table that the diaphragm optimized in this application is 0.6×106 N / m 2 ≤P / B≤29.9×10 6 N / m 2 , and preferably set 5×10 6 N / m 2 ≤P / B≤17.9×10 6 N / m 2 This is mainly to balance the improvement of the ion conductivity of the battery cell by the gap coating. The appropriate gap width can achieve better overall performance.
[0152] It can be seen from the results in the above table that in the diaphragm described in the present application, the interval width B of the ceramic strip layer is set to 6.7-50μm, and the peel strength P between the ceramic layer and the substrate layer is controlled to be in the range of 30-200N / m. The strong peel strength can ensure that the ceramic layer is not easily separated from the substrate, which means that the coating can remain stable under different environmental conditions, so that the battery can work stably under a wider range of temperature and humidity conditions, so that the available discharge depth of the battery remains constant under different environmental conditions and will not be affected by extreme conditions. For example, when the temperature and humidity conditions change, the available discharge depth of the battery remains unchanged, thereby improving the available discharge depth of the battery and reducing the minimum remaining charge (SOC) level that the battery can effectively supply power.
[0153] Example 5
[0154] The diaphragm described in this embodiment is as shown in the attached Figure 1 As shown, the base film is a polyethylene microporous film, the thickness D of the base film layer is 7 μm, and the puncture strength is 300 gf.
[0155] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the Dv50 of the ceramic particles is selected to be 0.3 μm, the coating thickness of the ceramic strip layer is controlled to be 1.5 μm, and the width A and the interval width B of the ceramic strip layer and the surface resistance R of the negative electrode of the lithium-ion secondary battery are respectively shown in Table 5 below.
[0156] The separator described in this example is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the minimum remaining capacity (SOC) (0° C.) that the lithium-ion secondary battery in each embodiment can effectively supply power is tested respectively. The specific method is the same as that in Example 3.
[0157] In this embodiment, the test results of various implementation methods are shown in Table 5 below.
[0158] Table 5 Relationship between width (A), gap width (B) and negative electrode surface resistance
[0159] serial number A(μm) B(μm) R(mΩ) A / R(μm / mΩ) B / R(μm / mΩ) Minimum effective discharge SOC (%) Example 5-1 30 20 20 1.5 1 31 Example 5-2 30 20 40 0.75 0.5 38 Example 5-3 30 20 60 0.5 0.33 43 Example 5-4 100 40 20 5 2 35 Example 5-5 30 6.7 60 0.5 0.11 46 Embodiment 5-6 100 50 20 5 2.5 34 Comparative Example 5-1 30 20 80 0.38 0.25 63 Comparative Example 5-2 30 6.7 80 0.38 0.08 68
[0160] It can be seen from the results in the above table that the surface resistance of the negative electrode sheet is a strongly correlated factor that determines the available discharge depth of the battery, which is mainly affected by the active material composition and particle size, conductive agent and binder used. Under normal circumstances, the larger the surface resistance, the more unfavorable it is for the battery to discharge, and the available discharge depth of the battery will be worsened. In the diaphragm described in the present application, the width A of the ceramic strip layer and the surface resistance R of the negative electrode are adjusted to satisfy the following relationship: 0.5μm / mΩ≤A / R≤5μm / mΩ, and the spacing width B of the ceramic strip layer and the surface resistance R of the negative electrode are adjusted to satisfy the following relationship: 0.11μm / mΩ≤B / R≤2.5μm / mΩ, which can effectively improve the discharge depth of the battery, reduce the minimum remaining power (SOC) level that the battery can effectively supply power, and the battery has a better available discharge depth.
[0161] In the present application, when the negative electrode surface resistance is within the range of 20-60mΩ, 0.5μm / mΩ≤strip width A / negative electrode surface resistance R≤5μm / mΩ is further controlled, which can effectively improve the discharge depth of the battery and reduce the minimum remaining power (SOC) level that the battery can effectively supply power, compared with the comparative example 5-1. Similarly, when 0.11μm / mΩ≤spacing width B / negative electrode surface resistance R≤2.5μm / mΩ, the battery also has a better available discharge depth.
[0162] Example 6
[0163] The diaphragm described in this embodiment is as shown in the attached Figure 1 As shown, the base film is a polyethylene microporous film, the thickness D of the base film layer is 7 μm, and the puncture strength is 300 gf.
[0164] In the diaphragm described in this embodiment, the required ceramic strip layer is coated according to the aforementioned exemplary preparation method, the Dv50 of the ceramic particles is selected to be 0.3μm, and the coating thickness of the ceramic strip layer is controlled to be 1.5μm. The width A of the ceramic strip layer, the interval width B, the ratio Q of the two, and the numerical value q of the lithium-ion secondary battery and min<the aspect ratio of the positive electrode tab groove q1, the aspect ratio of the negative electrode tab groove q2> are respectively shown in Table 6 below.
[0165] The separator described in this example is assembled according to the exemplary method of the aforementioned lithium-ion secondary battery, and the minimum remaining capacity (SOC) (0° C.) that the lithium-ion secondary battery in each embodiment can effectively supply power is tested respectively. The specific method is the same as that in Example 3.
[0166] In this embodiment, the test results of various implementation methods are shown in Table 6 below.
[0167] Table 6 Relationship between ratio Q and value q
[0168] serial number A(μm) B(μm) Q q1(mm) q2(mm) q(mm) Q / q Minimum effective discharge SOC (%) Example 6-1 30 20 1.5 3.75 6 3.75 0.4 35 Example 6-2 30 20 1.5 2.21 4 2.21 0.7 33 Example 6-3 30 20 1.5 0.67 3 0.67 2.2 30 Example 6-4 90 20 4.5 0.67 3 0.67 6.7 34 Example 6-5 90 20 4.5 2.21 4 2.21 2.1 37 Example 6-6 90 20 4.5 3.75 6 3.75 1.2 40 Comparative Example 6-1 30 20 1.5 4.50 6 4.50 0.3 57 Comparative Example 6-2 90 20 4.5 0.53 0.67 0.53 8.5 60
[0169] From the data in the table above, it can be seen that the size of the tab slot is a strongly correlated factor affecting the battery's charge and discharge capabilities. Usually, when the tab slot size is designed to be too small, it is often not conducive to the effective charge and discharge of the battery and deteriorates the battery's available discharge depth; and when the tab slot size is designed to be too large, the capacity of the battery cell will be lost. In this application, the aspect ratio q1 of the positive tab slot is adjusted to be within the range of 0.67-3.75, and the aspect ratio q2 of the negative tab slot is adjusted to be within the range of 0.67-6. In particular, when Q / q meets 0.4-6.7mm -1 range, the available discharge depth of the battery can be effectively improved and the minimum remaining charge (SOC) level at which the battery can effectively supply power can be reduced.
[0170] Furthermore, the width of the diaphragm-controlled pole ear groove described in the present application is between 5-15 mm and the length is between 10-30 mm, which further ensures the available discharge depth of the battery and reduces the minimum remaining charge (SOC) level at which the battery can effectively supply power.
[0171] In summary, the diaphragm described in the present application includes a base film, and at least two ceramic strip layers are coated on at least one side of the base film to form an interval. The diaphragm provided in the present application forms a ceramic strip layer by coating at least one surface of the base film, and by optimizing the parameters of the entire diaphragm, the migration rate of active ions in the electrolyte in the diaphragm is effectively improved, thereby improving the available discharge depth of the battery, improving the charge and discharge capacity of the battery, reducing the minimum remaining power (SOC) level that the battery can effectively supply power, and improving the application performance of the lithium-ion battery.
[0172] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A diaphragm, characterized in that: The diaphragm comprises a base film and a ceramic strip layer disposed in parallel and spaced apart on at least one side surface of the base film; The width of the ceramic strip layer is A, the puncture strength of the base film is N, and the relationship between A and N satisfies: 1 gf / μm≤N / A≤17 gf / μm.
2. The diaphragm according to claim 1, characterized in that: The relationship between A and N satisfies: 6gf / μm≤N / A≤13gf / μm; and / or, A satisfies: 30 μm ≤ A ≤ 100 μm; and / or, The N satisfies: 100gf≤N≤600gf; and / or, The number of the ceramic strip layers is ≥ 2; and / or, The ceramic strip layers are arranged in parallel along the length or width direction of the base film; and / or, The ceramic strip layers are arranged at equal intervals along the surface of the base film; and / or, The thickness of the ceramic strip layer is 0.5-5 μm.
3. The diaphragm according to claim 1, characterized in that The peel strength between the ceramic strip layer and the base film is P, the interval width between adjacent ceramic strip layers is B, and the relationship between P and B satisfies: 0.6×10 6 N / m 2 ≤P / B≤29.9×10 6 N / m 2 ; preferably, 5×10 6 N / m 2 ≤P / B≤17.9×10 6 N / m 2 ; Among them, 6.7μm≤B≤50μm, 30N / m≤P≤200N / m.
4. The diaphragm according to claim 1, characterized in that The width of the ceramic strip layer is A, the interval width of adjacent ceramic strip layers is B, and the ratio Q of A to B satisfies: 1.5≤Q≤4.5; Among them, 30μm≤A≤100μm, 6.7μm≤B≤50μm.
5. The diaphragm according to claim 4, characterized in that The ceramic strip layer includes ceramic particles; The particle size Dv50 of the ceramic particles is D, and the relationship between Q and D satisfies: 0.05 μm≤D / Q≤1.4 μm; preferably, 0.09 μm≤D / Q≤0.67 μm; Among them, 0.1μm≤D≤2.5μm.
6. The diaphragm according to any one of claims 1 to 5, characterized in that: The ceramic strip layer includes ceramic particles and a binder; Preferably, the ceramic particles include one or more of boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon dioxide (SiO2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), cerium oxide (CeO2), zirconium titanate (SrTiO3), barium titanate (BaTiO3), and magnesium fluoride (MgF2); Preferably, the binder includes one or more of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and trichloroethylene, polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, styrene-butadiene rubber, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polytetrafluoroethylene or polyhexafluoropropylene.
7. The diaphragm according to any one of claims 1 to 5, characterized in that: The base film satisfies at least one of the following conditions: a) Elongation at break TD is 20%-200%; b) elongation at break MD is 50%-300%; c) The thickness is 4 μm-20 μm.
8. A battery comprising a positive electrode, a negative electrode, an electrolyte and a separator between the positive electrode and the negative electrode; characterized in that: The diaphragm is the diaphragm according to any one of claims 1 to 7.
9. The battery according to claim 8, characterized in that The surface resistance of the negative electrode is R; A and R satisfy the following relationship: 0.5 μm / mΩ≤A / R≤5 μm / mΩ; and / or, B and R satisfy the following relationship: 0.11 μm / mΩ≤B / R≤2.5 μm / mΩ; Among them, 20mΩ≤R≤60mΩ.
10. The battery according to claim 8, characterized in that The positive electrode includes a positive electrode tab groove, and the negative electrode includes a negative electrode tab groove; the aspect ratio of the positive electrode tab groove is q1, and the aspect ratio of the negative electrode tab groove is q2, taking min<q1,q2> The value of is q, and the q and Q values satisfy the following relationship: Q / q = 0.4-6.7 mm -1 ; Among them, 0.67≤q1≤3.75, 0.67≤q2≤6.
11. The battery according to claim 10, characterized in that: The widths of the positive electrode tab groove and / or the negative electrode tab groove are independently 5-15 mm; and / or, The lengths of the positive electrode tab groove and / or the negative electrode tab groove are independently 10-30 mm.
12. A battery comprising a positive electrode, a negative electrode, an electrolyte and a separator between the positive electrode and the negative electrode; characterized in that: The diaphragm comprises a base film and a ceramic strip layer disposed in parallel and spaced apart on at least one side surface of the base film; The width of the ceramic strip layer is A, the interval width between adjacent ceramic strip layers is B, and the surface resistance of the negative electrode is R; A and R satisfy the following relationship: 0.5 μm / mΩ≤A / R≤5 μm / mΩ; and / or, B and R satisfy the following relationship: 0.11 μm / mΩ≤B / R≤2.5 μm / mΩ; Among them, 30μm≤A≤100μm, 6.7μm≤B≤50μm, 20mΩ≤R≤60mΩ.
13. The battery according to claim 12, characterized in that: The positive electrode includes a positive electrode tab groove, and the negative electrode includes a negative electrode tab groove; the aspect ratio of the positive electrode tab groove is q1, and the aspect ratio of the negative electrode tab groove is q2, taking min<q1,q2> The value of is q, the ratio of A to B is Q, and the q and Q values satisfy the following relationship: Q / q = 0.4-6.7 mm -1 ; Among them, 0.67≤q1≤3.75, 0.67≤q2≤6.
14. The battery according to claim 13, characterized in that: The widths of the positive electrode tab groove and / or the negative electrode tab groove are independently 5-15 mm; and / or, The lengths of the positive electrode tab groove and / or the negative electrode tab groove are independently 10-30 mm.
Citation Information
Patent Citations
Battery diaphragm and preparation method thereof
CN115810872A
Cylindrical battery
CN117039194A
Polyolefin-based membrane and preparation method thereof, diaphragm, secondary battery and electric device
CN118020206A
Novel lithium ion battery is with diaphragm
CN208674245U
Non-aqueous electrolyte secondary battery
JP2021068504A
Cited By
Battery cell and electrochemical device comprising same
CN120165186A
A battery cell and an electrochemical device including the battery cell.
CN120165186B
Separator and battery
WO2026179775A1
Battery cell and electrochemical device comprising same
WO2026194499A1
